An exploration of consumer attitude and sustainable purchase intention within the fashion industry. - Brickman, Stephanie (The IIE, 2022)
This research probed at the emerging intention-behaviour-gap in the sustainable purchasing decisions of consumers within the South African fashion industry, through an exploration of consumers attitude towards sustainability. Insight into this problem was guided, and gained, through the theory of planned behaviour (Aijzen, 1991), which supplemented exploration into the potential barriers to performing a behaviour such as attitude, subjective norms, and perceived behavioural control. The theory of planned behaviour (Aijzen, 1991) aided in cultivating, and guiding the development of, an understanding into consumer intention and actual performed behaviour, regarding sustainable purchasing decisions in the South African fashion industry. Insight into the problem of this emerging intention-behaviour-gap, was established through exploration into the perceptions of individual South African consumers regarding sustainability within the fashion industry. The results of this exploration indicate that South African consumer attitude towards sustainable purchasing behaviour within the fashion industry is highly favourable. The sample demonstrated a higher regarded for the subjective norm and opinions of their peers, than for their families with regards to sustainable purchasing behaviour within the fashion industry. The sample further demonstrated that the barriers to their perceived level of control, with regards to sustainable purchase intention within the South African fashion industry, were aesthetics, price, and accessibility. This demonstrates that there is an audience for sustainable fashion in South Africa; however, based on the exploration of this research, the market lusts after an improvement in aesthetic, accessibility, and price-point to incite intention. This research also revealed that members of the sample felt a sense of gratification post-sustainable-purchase, regardless of organisational transparency; however, transparency and honesty are also of prime importance to this audience prior-to-purchase. This is a potential gap in knowledge that could be explored in further research.
Keywords: Consumer behaviour; Buying behavior; Behavioral intention; Subjective norm; Sustainability